Community-Based Tsunami Disaster Risk Management in Ambon City - Halawa, Febermen; Lasaiba, Mohammad Amin; Riry, Johan (Jurnal Pendidikan Geografi Unpatti, 2022)
Community-based disaster risk management is used in reducing disaster risk and improving community resilience to tsunamis. This research was conducted in Ambon City which is a very vulnerable area of tsunami disaster. shown based on historical data. The method of collection used is secondary data with survey techniques using analytical techniques using content analysis. The results of the study showed that Ambon City Government had prepared itself by forming safety-conscious community groups in tackling tsunami threats and the level of recative community-based disaster risk management is quite good. Tsunami disaster risk management actions have been done in collaboration with related agencies such as BNPB, LIPI of Ambon City Government and research institutions from home and abroad.